Air pollution: Participatory elements in the development of an anxious animosity and ethical considerations of the psychological practice in Puerto Rico - Soto Ruiz, Xavier; Velázquez González, Héctor José; Vélez González, Verónica (Pensando Psicología, 2020)
Introduction: World Health Organization establishes that air pollution is the greatest environmental threat to physical human health.Aim: To critically reflect on psychological implications of air pollution. It was weighted air pollution perception against anxiety symptoms, with a special look on Puerto Ricans inhabitants.Method: a theoretical review between 1990 and 2018 was carried out and also a reflection on the findings with special attention to psychology’s role as a discipline that promotes social transformation.Results: air pollution affects countries worldwide. It is not known which period of time counts as biologically relevant to be exposed to particulate matter. A prolonged exposure could have greater effects on mental health. Air pollution and anxiety symptoms has been studied recently, although without conclusive empirical evidence.Conclusions: reflect on the consequences of air pollution on mental health is worthy if one aspires to a better quality of life and a healthy environment. A call is made to psychological community to consider environmental factors in the clinical context as variables that have an impact on the individual’s well being and behavior, to consider alternate therapetics and to perform an active role in community’s fights.
Keywords: axienty; particulate matter; pollution perception; air pollution